Increasing workers’ safety by using Virtual Reality (VR) in the project design and production planning - HUSEYNLI, AYTAN; TASNIM, IRINA (My University, 2023)
Construction sites pose inherently hazardous work environments due to the nature of the work involved. As such, the industry is known for its high rate of accidents and injuries compared to other industries which makes improving the safety of construction workers of paramount importance. This study examines the use of cutting-edge virtual reality (VR) technology to enhance the safety planning of construction projects in the design and planning phase. The study is built on a qualitative approach based on a literature review and an empirical study. The empirical study includes a workshop with two design engineers, a health and safety engineer, a VDC Developer and several researchers as participants. The findings from this study indicate that VR offers significant advantages over traditional 2D drawings in terms of safety planning. Immersive VR walkthrough can provide a more comprehensive representation of the project, aiding in the planning and implementation of effective safety measures. Moreover, the findings highlight that collaborative VR walkthroughs have the potential to enhance safety planning by improving communication and coordination among project stakeholders and the use of VR can increase safety awareness among design engineers, equipping them with the knowledge and mindset necessary to proactively address potential hazards. The study recommends the combination of VR with touchscreen boards for effective site planning and collaboration, acknowledging that VR technology is an immature technology which requires further research and advancement. Additionally, the study identifies some areas where future research should focus on.
Keywords: collaboration, construction, design engineer, hazards, safety, virtual reality, 2D drawing.